Dating violence: perpetration, and mutual violence. A review - Alegría del Ángel, Manoella (2015)
There are investigations whose results show similar rates of violence between men and women, including mutual violence, which are opposing to theories that refer to traditional gender roles. The aim of this study was to perform a theoretical review about the main findings of dating violence in Latin countries and North America from a gender inclusive perspective. Studies since 2000 to 2013 were included, the search was performed in databases. It was concluded that sociocultural changes require performing a different approach to violence in young, considering an inclusive vision to promote relationships of nonviolence. It is recommended to deepen in the paper of gender roles.